1984
DOI: 10.1017/s0025315400030095
|View full text |Cite
|
Sign up to set email alerts
|

The effect of copper and zinc on the shell growth of Mytilus edulis measured by a laser diffraction technique

Abstract: The effects of copper and zinc on the daily shell growth of Mytilus edulis have been measured with a laser diffraction measuring technique accurate to 3 µm. The results show that within three days 10 ppb added copper has a significant inhibitory effect on shell growth. Longer term experiments have been undertaken which show that the effects of 10 ppb added copper become more severe as exposure time increases. Recovery of near normal shell growth does occur on transfer to clean sea water even after a 14 day exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Field studies (Widdows et al 1987) and mesocosm studies (Widdows et al 1985) have demonstrated that petroleum hydrocarbons, particularly aromatic hydrocarbons, accumulated in the tissues of M. edulis depress clearance rate and SFG over a wide range of concentrations, representing more than 3 orders of magnitude, with no evidence of a threshold effect. In contrast to petroleunl hydrocarbons, Cu appears to exert sublethal effects on feeding and growth rates of M. edulis over a relatively narrow range of water concentrations (less than 1 order of magnitude) with a threshold of effect at ca 5 to 10 pg Cu 1-' and a marked inhibition at 20 pg Cu 1-' (Manley 1983, Calabrese et al 1984, Manley et al 1984, Redpath 1985. Therefore it appears that Cu concentrations in L and M conditions were below the threshold of effect, and that the extent of the decline in clearance rate (L: 5 %, M: 20 %; approximately) and SFG, measured in L and M mussels, can b e entirely explained by the hydrocarbon concentrations.…”
Section: Discussionmentioning
confidence: 97%
“…Field studies (Widdows et al 1987) and mesocosm studies (Widdows et al 1985) have demonstrated that petroleum hydrocarbons, particularly aromatic hydrocarbons, accumulated in the tissues of M. edulis depress clearance rate and SFG over a wide range of concentrations, representing more than 3 orders of magnitude, with no evidence of a threshold effect. In contrast to petroleunl hydrocarbons, Cu appears to exert sublethal effects on feeding and growth rates of M. edulis over a relatively narrow range of water concentrations (less than 1 order of magnitude) with a threshold of effect at ca 5 to 10 pg Cu 1-' and a marked inhibition at 20 pg Cu 1-' (Manley 1983, Calabrese et al 1984, Manley et al 1984, Redpath 1985. Therefore it appears that Cu concentrations in L and M conditions were below the threshold of effect, and that the extent of the decline in clearance rate (L: 5 %, M: 20 %; approximately) and SFG, measured in L and M mussels, can b e entirely explained by the hydrocarbon concentrations.…”
Section: Discussionmentioning
confidence: 97%
“…Manley et al 1984, Redpath 1985, where E:C = 1nLexp, X 100/lnL,,,,,,l (L = Age (days) length of the animals). The assumption is experimental animal is that of the control and that any vai-lations in environmental conditions will affect the rate of the growth of control and experimental animals equally.…”
Section: Methodsmentioning
confidence: 99%
“…Copper concentrations of 30 l g 1-I were shown by Manley (1983) to cause a 50 % reduction in normal filtration activity, and 10 to 20 kg 1-I were noted as causing serious impairment to growth and, ultimately, death. Manley et al (1984), using a laser diffraction measuring technique, showed that as little as 10 ppb had a significant inhibitory effect on shell growth. As the ratio of freshwater to seawater increased, the influence of copper concentration exceeded that of the reduced salinity on byssus production.…”
Section: Methodsmentioning
confidence: 99%